Potential Mechanisms of the Impact of Hepatocyte Growth Factor Gene-Modified Tendon Stem Cells on Tendon Healing - Zhang, Mingzhao; Liu, Hengchen; Shi, Manyu; Zhang, Tingting; Lu, Wenjun; Yang, Shulong; Cui, Qingbo; Li, Zhaozhu (Frontiers in Cell and Developmental Biology, 2021)
The therapeutic impact of stem cells is potentially largely attributable to secretion of exosomes and soluble factors. The present study evaluated the impact of hepatocyte growth factor (HGF)-expressing tendon stem cells (TSCs) on tendon healing in a rat model. Patellar tendon TSCs were isolated and underwent transfection with lentiviral vectors containing HGF or green fluorescent protein (GFP) genes. In vivo, immunohistochemistry of tendons sampled one week post-surgery demonstrated that all stem cell-treated groups exhibited higher numbers of CD163+ M2 monocytes and IL-10+ cells (anti-inflammatory), and lower numbers of CCR7+ M1 monocytes and IL-6+ as well as COX-2+ cells (pro-inflammatory). Effects were most pronounced in the HGF-expressing TSCs (TSCs+HGF) treated group. Histology ± immunohistochemistry of tendons sampled four and eight weeks post-surgery demonstrated that all stem cell-treated groups exhibited more ordered collagen fiber arrangement and lower levels of COLIII, α-SMA, TGF-β1, and fibronectin (proteins relevant to fibroscarring). Effects were most pronounced in the TSCs+HGF-treated group. For the in vitro study, isolated tendon fibroblasts pretreated with TGF-β1 to mimic the in vivo microenvironment of tendon injury were indirectly co-cultured with TSCs, TSCs+GFP, or TSCs+HGF using a transwell system. Western blotting demonstrated that all stem cell types decreased TGF-β1-induced increases in fibroblast levels of COX-2, COLIII, and α-SMA, concomitant with decreased activation of major TGF-β1 signaling pathways (p38 MAPK, ERK1/2, but not Smad2/3). This effect was most pronounced for TSCs+HGF, which also decreased the TGF-β1-induced increase in activation of the Smad2/3 signaling pathway. The presence of specific inhibitors of these pathways during fibroblast TGF-β1 stimulation also attenuated increases in levels of COX-2, COLIII, and α-SMA. In conclusion, TSCs+HGF, which exhibit sustained HGF secretion, may promoting tendon healing via decreasing inflammation and fibrosis, perhaps partly via inhibiting TGF-β1-induced signaling. These findings identify a novel potential therapeutic strategy for tendon injuries, warranting additional research.